Analisis Yuridis terhadap Praktik Jual Beli Akun Mobile Legends: Bang Bang Ditinjau dari Hukum Perdata Indonesia - Edvaldo Jose Luis Soares Sequeira; Dewa Ayu Putri Sukadana; Ni Putu Sawitri; Kadek Julia Mahadewi (Cattleya Darmaya Fortuna, 2025)
This study examines the legal status and position of Mobile Legends: Bang Bang (MLBB) game accounts as objects of sale and purchase under Indonesian civil law. The increasing practice of game account trading raises legal questions, as it is not explicitly regulated within existing laws. The research applies a normative legal method, focusing on the analysis of positive legal norms or law in the book (Muhaimin, 2020). The study uses both statutory and conceptual approaches, referring to the Indonesian Civil Code (KUHPerdata), Law No. 8 of 1999 on Consumer Protection, Law No. 11 of 2008 jo. Law No. 19 of 2016 on Electronic Information and Transactions, and Government Regulation No. 71 of 2019 (Yati Nurhayati et al., 2021). Data were collected through library research and analyzed qualitatively (Peter Mahmud Marzuki, 2017). The results show that the sale of MLBB accounts meets the contractual elements in Articles 1320 and 1457 of the Civil Code—consent, capacity, clear object, and economic value. The account can be seen as intangible property with economic worth; however, legal ownership remains with the developer, Moonton, who only grants access through a license agreement. Thus, the transaction is valid between users but lacks binding legal force against the developer when violating the Terms of Service. The study concludes that MLBB account trading is legally valid in a limited sense within civil relations but not formally recognized in Indonesian law. This highlights the need for civil law reform to accommodate digital economic developments and acknowledge virtual assets as legitimate legal objects.